ECERDC UMP Cucumber Fertigation Project empowers socioeconomy of Orang Asli - Nor Salwana, Mohammad Idris (UMPSA, 2023)
LIPIS, 9 April 2023 – The Cucumber Fertigation Project undertaken by the East Coast Economic Region Development Council (ECERDC) and UMP Advanced with Orang Asli of Kampung Pantos has achieved the goal of strengthening the socioeconomy of Orang Asli through encouraging outcomes.